1995
DOI: 10.7863/jum.1995.14.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal color and pulsed Doppler sonography of the endometrium: a possible role in reducing the number of dilatation and curettage procedures.

Abstract: The objectives of the study were to establish color and pulsed Doppler sonographic characteristics of uterine vascularity in postmenopausal patients with pathologic endometrium in order to reduce the number of unnecessary diagnostic dilatation and curettage procedures. The prospective study involved 42 postmenopausal patients who were examined, prior to dilatation and curettage operation, with transvaginal color and pulsed Doppler sonography. Twenty patients had symptoms such as vaginal bleeding or clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 0 publications
1
14
1
Order By: Relevance
“…Aleem et al 13 also found RI and PI were significantly less in the cases of endometrial hyperplasia. Alcazar et al 14 in his study found that the endometrial volumes were significantly higher in malignant conditions.…”
Section: Resultsmentioning
confidence: 86%
“…Aleem et al 13 also found RI and PI were significantly less in the cases of endometrial hyperplasia. Alcazar et al 14 in his study found that the endometrial volumes were significantly higher in malignant conditions.…”
Section: Resultsmentioning
confidence: 86%
“…The rationale for removing symptomatic polyps in patients is to rule out malignancy and obtain relief from associated symptoms. Some authors suggested that evaluation of tissue vascularization by color Doppler imaging may be useful in predicting malignant endometrial changes, as malignancy is associated with increased blood flow [14,15] . Similarly, low blood flow resistance is reported to be predictive of atypical endometrial polyps [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many reports have confirmed the ability of Doppler imaging to show aberrant neovascularization. [8][9][10]15 The ability to measure a flow waveform inside the stalk has permitted us to apply these principles to EPs. Using an arbitrary cutoff RI value of 0.5, we achieved good specificity.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Some studies suggest that color flow Doppler imaging may assist in the diagnosis of endometrial carcinoma, because blood flow is increased in malignant lesions. 9,10 Some EPs show color maps reflecting functional activity. The efficacy of the color map to assess functional activity in opposition to an atrophic pattern has been reported previously.…”
mentioning
confidence: 99%